2019
DOI: 10.1186/s12877-019-1037-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of smartphone and smartband technology in the improvement of lifestyles in the adult population over 65 years: study protocol for a randomized clinical trial (EVIDENT-Age study)

Abstract: BackgroundThe increasing use of smartphones by older adults also increases their potential for improving different aspects of health in this population. Some studies have shown promising results in the improvement of cognitive performance through lifestyle modification. All this may have a broad impact on the quality of life and carrying out daily living activities. The objective of this study is to evaluate the effectiveness of combining the use of smartphone and smartband technology for 3 months with brief c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Finally, as the last search was conducted in April 2018, it is possible that more recent trials were not included. We conducted a rapid literature search in PubMed in March 2020 looking for potentially relevant studies published after the last update and identified one published study [89] and six published protocols [90][91][92][93][94][95], which indicates that several trials of e-Health interventions for HA are currently ongoing. We thus recommend to update this systematic review within the next 2 years as more evidence is likely to change the conclusions of the present systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as the last search was conducted in April 2018, it is possible that more recent trials were not included. We conducted a rapid literature search in PubMed in March 2020 looking for potentially relevant studies published after the last update and identified one published study [89] and six published protocols [90][91][92][93][94][95], which indicates that several trials of e-Health interventions for HA are currently ongoing. We thus recommend to update this systematic review within the next 2 years as more evidence is likely to change the conclusions of the present systematic review.…”
Section: Discussionmentioning
confidence: 99%
“… The subjects had to be at the age 55+ years old. The exclusion criteria were as follows: The review studies [ 10 , 16 , 17 , 18 ], slightly different research focus [ 19 ], multi-domain intervention studies [ 9 , 20 , 21 ], study protocols [ 22 , 23 ], the studies outside the determined period [ 11 , 12 ] or the studies with different age of participants [ 24 ]. …”
Section: Methodsmentioning
confidence: 99%
“…The patients with cardiometabolic disease studied reported that lifestyle-targeting text messaging approaches were feasible and acceptable, and that the text messages were easy to understand (88%) and were sent at an Connected Health Interventions to Cardiovascular Disease Prevention Agher et al 549 appropriate frequency (71%), in appropriate language (88%). Most of the studies used "smartphone health applications (connect)" [8][9][10][11][12]15,16,19,20,22,[24][25][26][27] . "Focus group" (do) and "Education" (read) were used together in two articles.…”
Section: Connected Health Interventionmentioning
confidence: 99%
“…In six articles, "moderate adherence" (orange line) was achieved. 8,14,17,[22][23][24] Five articles did not mention or evaluate adherence. These articles are indicated by gray lines as "adherence unknown" in ►Fig.…”
Section: Adherencementioning
confidence: 99%